2007
DOI: 10.1051/0004-6361:20077778
|View full text |Cite
|
Sign up to set email alerts
|

The XMM large scale structure survey: optical vs. X-ray classifications of active galactic nuclei and the unified scheme

Abstract: Aims. Our goal is to characterize AGN populations by comparing their X-ray and optical classifications within the framework of the standard orientation-based unified scheme. Methods. We present a sample of 99 spectroscopically identified (R ≤ 22 mag) X-ray selected point sources in the XMM-LSS survey which are significantly detected (≥3σ) in the [2−10] keV band with fluxes between 8 × 10 −15 and 8 × 10 −14 erg s −1 cm −2 , and which have more than 80 counts. We have compared their X-ray and optical classificat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
42
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 80 publications
11
42
1
Order By: Relevance
“…However, Risaliti et al (1999) found an even smaller fraction of only 4%. On the contrary, Marinucci et al (2012) claimed that the fraction of unobscured Sy2 in their sample in about 40% and Page et al (2006) and Garcet et al (2007) reported an even higher fraction of about 66%−68%.…”
Section: Introductionmentioning
confidence: 95%
“…However, Risaliti et al (1999) found an even smaller fraction of only 4%. On the contrary, Marinucci et al (2012) claimed that the fraction of unobscured Sy2 in their sample in about 40% and Page et al (2006) and Garcet et al (2007) reported an even higher fraction of about 66%−68%.…”
Section: Introductionmentioning
confidence: 95%
“…We also report in this diagram the values obtained for a sample of the brightest 99 hard X-ray sources detected in the XMM-LSS survey (e.g. Garcet et al 2007). This survey covers ∼6 deg 2 and, therefore, is one of the surveys with the widest coverage area in X-rays.…”
Section: X-ray To Optical Flux Ratiomentioning
confidence: 99%
“…The median value of probXO for ext, ptl, stars, and mcl objects is 0.018, 0.009, 0.0002 and 0.109, respectively. Tajer et al (2007) and Garcet et al (2007) ranked the probability of counterparts as good (probXY < 0.01), fair (0.01 < probXY < 0.03) and bad (probXY > 0.03). We thus see that our mcl objects naturally fall in the latter category.…”
Section: The Sample Of X-ray Sources and Their Counterpartsmentioning
confidence: 99%
“…deg XMM-Large Scale Structure (LSS) medium-deep extragalactic survey. Earlier versions of our survey over a lower solid angle and a variety of analyses can be found in Chiappetti et al (2005), Gandhi et al (2006), Pierre et al (2007), Tajer et al (2007), Polletta et al (2007), Garcet et al (2007), Tasse et al (2008a,b) and Nakos et al (2009).…”
Section: Introductionmentioning
confidence: 99%